Women and Rural Medical Practice - J. Wainer; D. Carson; R.P. Strasser (South African Family Practice)
The shortage of rural doctors affects many countries, including South Africa. Medical workforce planners have introduced various strategies to encourage or compel doctors to practise in under served areas. One of the strategies is to respond to the increasing presence of women as doctors by seeking to understand how women practise medicine, and how rural practice has to change to attract women.